Islamisasi Pengetahuan dan Model Pengembangannya pada Madrasah - Mukhibat, Mukhibat (Nadwa, 2013)
Madrasah in Indonesia have exciting development because of its integration with modernity and political support of the state that aligned with the public schools. However, it is recognized that the model of madrasah education in the countrys legislation, led to dualism education system in Indonesia, which has not been resolved until now. The problem is a challenge in realizing the ideal madrasah. Through a historical-philosophical approach, this study examines the redefinition of the Islamization of knowledge by tracing historically the initial idea of Islamization of knowledge in responding to the challenges facing the madrasah. Through critical analysis examines the implications of the redefinition of the Islamization of knowledge and development models at the madrasah. There are at least three models of Islamization of knowledge that can be developed in the development and empowerment of the madrasah, the purification of the model, the model of modernization, and the model of Islamic neo-modernism.